Synthesis, optimization, and cell response investigations of natural-based, thermoresponsive, injectable hydrogel: An attitude for 3D hepatocyte encapsulation and cell therapy - Gholami, Mahnaz; Tajabadi, Maryam; Khavandi, Alireza; Azarpira, Negar (Frontiers in Bioengineering and Biotechnology, 2023)
For the purpose of developing a 3D vehicle for the delivery of hepatocytes in cell therapy, the improved system of crosslinker and new gelling agent combinations consisting of glycerophosphate and sodium hydrogen carbonate have been employed to produce injectable, thermoresponsive hydrogels based on chitosan and silk fibroin. Adjusting the polymer-to-gelling agent ratio and utilizing a chemical crosslinker developed hydrogel scaffolds with optimal gelling time and pH. Applying sodium hydrogen carbonate neutralizes chitosan while keeping its thermoresponsive characteristics and decreases glycerophosphate from 60% to 30%. Genipin boosts the mechanical properties of hydrogel without affecting the gel time. Due to their stable microstructure and lower amine availability, genipin-containing materials have a low swelling ratio, around 6 compared to 8 for those without genipin. Hydrogels that are crosslinked degrade about half as fast as those that aren't. The slower degradation of Silk fibroin compared to chitosan makes it an efficient degradation inhibitor in silk-containing formulations. All of the optimized samples showed less than 5% hemolytic activity, indicating that they lacked hemolytic characteristics. The acceptable cell viability in crosslinked hydrogels ranges from 72% to 91% due to the decreasing total salt concentration, which protects cells from hyperosmolality. The pH of hydrogels and their interstitial pores kept most encapsulated cells alive and functioning for 24 hours. Urea levels are higher in the encapsulation condition compared to HepG2 cultivated alone, and this may be due to cell-matrix interactions that boost liver-specific activity. Urea synthesis in genipin crosslinked hydrogels increased dramatically from day 1 (about 4 mg.dL-1) to day 3 (approximately 6 mg.dL-1), suggesting the enormous potential of these hydrogels for cell milieu preparation. All mentioned findings represent that the optimized system may be a promising candidate for liver regeneration.